Pengaruh Harga dan Promosi terhadap Keputusan Pembelian HokBen Cabang Kota Palembang - Pratama, Rizky Arya; Megawati, Megawati (Universitas Multi Data Palembang, 2025)
This study aims to analyze the effect of price and promotion on consumer purchase decisions at HokBen Palembang branch. In the increasingly competitive fast food industry, effective marketing strategies play a crucial role in attracting customers. Competitive pricing and appealing promotions can enhance purchase interest and influence consumer decision-making. This research employs a quantitative method with a survey approach, collecting data through questionnaires distributed to 400 respondents. Multiple linear regression analysis is used to examine the relationship between price, promotion, and purchase decisions. The results indicate that price and promotion have a positive and significant impact on purchase decisions, both partially and simultaneously. These findings highlight the importance of implementing appropriate pricing strategies and innovative promotions to enhance product appeal and foster consumer loyalty toward HokBen.